2009
DOI: 10.1002/ca.20847
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous perforators of the peroneal artery: Cadaveric study with implications in the design of the osteocutaneous free fibular flap

Abstract: Bilateral dissection of 15 formalin embalmed cadaver legs was performed in order to study the anatomic pattern of the peroneal artery (PA) and its cutaneous perforating vessels (CB). The total number of CB from the PA was 125 or an average of 4.17 branches per leg. CB were distributed in the superoinferior axis between 18.25 and 84.25% of the length of the fibula and their average length was 5 +/- 1.8 cm. 86/125 (68.8%) of the CB were classified as myocutaneous branches (MC) that penetrated muscle before reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…In a similar study, Papadimas et al evaluated 30 cadaveric legs and identified a total of 125 cutaneous perforating vessels, with an average of 4.17 branches per leg. 11 The authors went on to conclude that the highest density of perforators was in the 0.6 to 0.7 interval (mean fibular length, 37 cm) and that, based on this, a fibular skin paddle would be best centered at the boundary between the middle and distal thirds of the fibula. Cho et al verified these cadaveric results in the clinical setting by recording the perforators in 24 patients undergoing free fibula osteocutaneous transfer for femoral head osteonecrosis.…”
Section: Plastic and Reconstructive Surgery • September 2012mentioning
confidence: 98%
“…In a similar study, Papadimas et al evaluated 30 cadaveric legs and identified a total of 125 cutaneous perforating vessels, with an average of 4.17 branches per leg. 11 The authors went on to conclude that the highest density of perforators was in the 0.6 to 0.7 interval (mean fibular length, 37 cm) and that, based on this, a fibular skin paddle would be best centered at the boundary between the middle and distal thirds of the fibula. Cho et al verified these cadaveric results in the clinical setting by recording the perforators in 24 patients undergoing free fibula osteocutaneous transfer for femoral head osteonecrosis.…”
Section: Plastic and Reconstructive Surgery • September 2012mentioning
confidence: 98%
“…Concerning the lower leg, previous studies have mostly focused on perforators originating from a single source vessel . Peroneal artery perforators have been extensively described resulting in further refinements of the fibula osteocutaneous flap .…”
Section: Discussionmentioning
confidence: 99%
“…Papadimas et al found an average of 4.17 ± 0.9 peroneal artery perforators per leg. Perforators were distributed in the supero‐inferior axis between 18.25 and 84.25% of the length of the fibula . Their average length was 5 ± 1.8 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent years, studies in clinical anatomy have produced valuable information on specific vascularization of the anatomical structures used in these flaps (Saadeh et al, 1998;Fróes et al, 1999;Traxler et al, 1999;Tao et al, 2000;Halim and Wan, 2004;Macchi et al, 2008Macchi et al, , 2009Rozen et al, 2008Rozen et al, , 2009Rozen et al, , 2010Rozen et al, , 2011Ger, 2009;Ma et al, 2009;Papadimas et al, 2009;Beer and Manestar, 2010;Piquilloud et al, 2011;Janus et al, 2012).…”
mentioning
confidence: 99%